The effects of the die half angle of taper die on plane strain extrusion - Zuan, A. M. S. (Penerbit UTM Press, 2016)
In this research, a study of the effect of a die half angle on the extrusion process has been performed. The experiments were conducted at room temperature around 27 °C. Two types of taper die with different die half angles (45° and 60°) were prepared. The test lubricants used were paraffinic mineral oil VG460 and Refined, Bleached and Deodorized (RBD) Palm stearin. The material of the workpiece (billet) was annealed with A1100 aluminium. The experimental results were focused on the extrusion load, tool and workpiece surface roughness and plastic deformation of the workpiece. The resultant relative velocity was calculated using a visioplasticity method. The results shows that a taper angle of 60° recorded higher resultant relative velocity with a lower extrusion load and surface roughness compare to the taper angle of 45°. The comparison study between Paraffinic Mineral Oil and RBD Palm Stearin shows no significant effect in both taper angles tested.